(untitled) (Functional Plant Breeding Journal, 2022)
This article shows a feasibility study with a new proposal on the master plan for Itaperuna-RJ. An attempt was made to synthesize, through means of analysis and studies, the urban needs of a municipality. For this purpose, a real land with an existing urban context was chosen. After analyzing these indicators, it is concluded that the current form of zoning in the city is inefficient and a new zoning proposal appears aimed at the specificities of each region. Following the theoretical parameters about model cities, more humane and healthier new forms of organization for the city were devised. Tests were proposed on how dense and non-dense areas should behave to provide a more humanized city. It was found that in the city of Itaperuna-RJ, the current zoning and master plan do not provide adequate functionality or spatiality for the city.